2013
DOI: 10.1515/flin.2013.015
|View full text |Cite
|
Sign up to set email alerts
|

Arguing for a wide conception of grammar: The case of final particles in spoken discourse

Abstract: The grammatical status of final particles in spoken English, such as then, though, anyway, and but, is undefined, as the various labels used in the literature (e.g. connectors, linking adverbials, conjuncts) show. This indeterminacy derives from the functional diversity of these particles. They not only link units of (spoken) discourse, but may also create a link between a discourse unit and an implied proposition; they are used to express subjective meanings and to modify illocutionary force. As such partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…However, boosting the efficiency of this assumption is contingent on comparative and intra‐language studies on various discourse units. Moreover, as mentioned in this study, some previous research has shown that the correlation between the function types of language elements and their positions may be influenced by their inherent meaning and context (Traugott 2004), communication tasks (Haselow 2013, 2016), and turn sequencing (Heritage 1984, 2002), so more studies are required to determine the effects of such variables as language family, word order, and language channel (speaking versus writing).…”
Section: Discussionmentioning
confidence: 90%
“…However, boosting the efficiency of this assumption is contingent on comparative and intra‐language studies on various discourse units. Moreover, as mentioned in this study, some previous research has shown that the correlation between the function types of language elements and their positions may be influenced by their inherent meaning and context (Traugott 2004), communication tasks (Haselow 2013, 2016), and turn sequencing (Heritage 1984, 2002), so more studies are required to determine the effects of such variables as language family, word order, and language channel (speaking versus writing).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, they cannot be uncontroversially attributed to pre-established natural-kind-like cross-linguistic categories such as modal particles and discourse particles. Another interesting development in a similar field to be mentioned here is the idea that discourse-structuring devices are better treated as part of grammar rather than lexicon and are in principle not very different in nature from the "core" grammatical categories (Diewald 2006;Haselow 2013). As the latter, they provide cues to the listener about how the communicated concepts are to be "glued" together or interpreted within a concrete linguistic and extralinguistic context.…”
Section: Morphosyntactic Classification 21 General Contextmentioning
confidence: 90%
“…Heine et al 2013, Fernandez Vest 2015. It has also been suggested, for English, that RP particles now constitute a formal paradigm (Haselow 2013).…”
Section: Pourmentioning
confidence: 99%